2024
DOI: 10.1002/ehf2.14581
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of ivabradine in Chinese patients with chronic heart failure: an observational study

Jingmin Zhou,
Yamei Xu,
Zhaofen Zheng
et al.

Abstract: AimsA therapeutic strategy for chronic heart failure (HF) is to lower resting heart rate (HR). Ivabradine is a well‐known HR‐lowering agent, but limited prospective data exist regarding its use in Chinese patients. This study aimed to evaluate the effectiveness and safety of ivabradine in Chinese patients with chronic HF.Methods and resultsThis multicentre, single‐arm, prospective, observational study enrolled Chinese patients with chronic HF. The primary outcome was change from baseline in HR at 1 and 6 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…For example, a multi-centered study in 1853 older patients (age range 61–77) in Germany conducted from 2009 to 2011 reported that 71.0% of the participants were treated with beta-blockers at admission and 89% at discharge 23 . In a study of 1003 patients (mean age 54.4 ± 15.0) recruited from 2016 to 2019 in China, the prescription rate of beta-blockers in hospitalized patients with HFrEF was 84.2% 24 . The younger age of the participants and the fact that patients with heart rates < 75 bpm were excluded from that study may explain a higher prescription rate compared to our study 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a multi-centered study in 1853 older patients (age range 61–77) in Germany conducted from 2009 to 2011 reported that 71.0% of the participants were treated with beta-blockers at admission and 89% at discharge 23 . In a study of 1003 patients (mean age 54.4 ± 15.0) recruited from 2016 to 2019 in China, the prescription rate of beta-blockers in hospitalized patients with HFrEF was 84.2% 24 . The younger age of the participants and the fact that patients with heart rates < 75 bpm were excluded from that study may explain a higher prescription rate compared to our study 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 1003 patients (mean age 54.4 ± 15.0) recruited from 2016 to 2019 in China, the prescription rate of beta-blockers in hospitalized patients with HFrEF was 84.2% 24 . The younger age of the participants and the fact that patients with heart rates < 75 bpm were excluded from that study may explain a higher prescription rate compared to our study 24 .…”
Section: Discussionmentioning
confidence: 99%